2002
DOI: 10.1034/j.1399-3011.2002.02988.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure−affinity relationships in the gp41 ELDKWA epitope for the HIV‐1 neutralizing monoclonal antibody 2F5: effects of side‐chain and backbone modifications and conformational constraints

Abstract: The human monoclonal antibody, mAb 2F5, has broad HIV-1 neutralizing activity and binds a conserved linear epitope within the envelope glycoprotein gp41 having a core recognition sequence ELDKWA. In this study, the structural requirements of this epitope for high-affinity binding to mAb 2F5 were explored using peptide synthesis and competitive enzyme-linked immunosorbant assay (ELISA). Expansion of the minimal epitope to an end-capped, linear nonapeptide, Ac-LELDKWASL-amide, was sufficient to attain maximal af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
53
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 58 publications
10
53
1
Order By: Relevance
“…Since then, protease protection, phage display, and peptide binding experiments have shown its epitope to be larger (2,46,59,68), with addition of the two leucines flanking the core epitope increasing the affinity of 2F5 by 2,000-fold (59). The affinity of 2F5 for the membrane-proximal region is also enhanced when gp41 is presented in the presence of lipid (21), suggesting that the idiotope of the membrane-proximal region in vivo may depend on the presence of membrane.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Since then, protease protection, phage display, and peptide binding experiments have shown its epitope to be larger (2,46,59,68), with addition of the two leucines flanking the core epitope increasing the affinity of 2F5 by 2,000-fold (59). The affinity of 2F5 for the membrane-proximal region is also enhanced when gp41 is presented in the presence of lipid (21), suggesting that the idiotope of the membrane-proximal region in vivo may depend on the presence of membrane.…”
mentioning
confidence: 93%
“…These include nuclear magnetic resonance (NMR) studies of the membrane-proximal region (2,3) and crystal structures of 2F5 alone or in complex with a core 7-mer peptide (5,44). These studies have generally shown that the core epitope contains a ␤-turn conformation and have subsequently led to the hypothesis that cyclically constrained immunogens might more accurately mimic the 2F5 epitope and thus might more effectively induce 2F5-like neutralizing antibodies (36,59). However, immunogenic studies based on the 7-mer core epitope, using cyclically constrained peptides, have thus far failed to elicit broadly neutralizing antibodies (36).…”
mentioning
confidence: 99%
“…However, the role of the presence of lipids in recognition of epitopes during the membrane fusion has not yet been clearly elucidated. The 2F5 epitope contains a -turn conformation and antigen which is presented in a similar context may better mimic the epitope and consequently improve the binding of this Ab (Tian et al, 2002). Several difficulties rise to make a stable immunogen, flexible and mimicking faithfully the MPER in a native conformation sported during the steps of rapprochement and viral fusion process.…”
Section: Mper (Membrane-proximal External Region)mentioning
confidence: 99%
“…Studies have shown, for expression library and protection against proteases, that this epitope is wider (EQELLELDKWASLWN). By addition of a leucine at each side (LELDKWASL), the affinity for its epitope is increased by more than 2000 times (Ofek et al, 2004;Parker et al, 2001;Tian et al, 2002). In models that study the involvement of the viral membrane using POPC (1-oleyl-2-palmolityl-sn-glycero-3-phosphocholine) and POPC/cholesterol in the recognition and binding to its epitope, it has been shown that 2F5 does not interact with the membrane before fixation (Veiga and Castanho, 2006).…”
Section: Mper (Membrane-proximal External Region)mentioning
confidence: 99%
“…an α-aminoisobutyric (Aib) residue], by side-chain cross-linking or "stapling", and the use of helix caps and hydrogen bond surrogates. Some of these approaches have been explored already in vaccine design efforts, for example, the use of Aib residues to favour helical turns, hydrazone crosslinks as hydrogen bond surrogates, Freidinger-like lactams and pseudoprolines to stabilize turns, and cross-linked side-chains to stabilize helical epitopes [158][159][160][161][162][163][164][165]. β-Hairpin mimetics might also be very useful in synthetic vaccine design.…”
Section: Epitope Mimeticsmentioning
confidence: 99%